Automated detection and classification of beaked whale buzzes on bottom-mounted hydrophones - Jarvis, Susan M.; DiMarzio, Nancy; Watwood, Stephanie; Dolan, Karin; Morrissey, Ronald (Frontiers in Remote Sensing, 2022)
Beaked whales, like many other odontocetes, produce bouts of very rapid clicking that serve as a homing signal just prior to a prey capture attempt. For Blainville's and Cuvier's beaked whales (Mesoplodon densirostris, Md, and Ziphius cavirostris, Zc, respectively) these homing sequences have been dubbed “buzzes.” Buzz clicks have both a structure that is markedly different from and a source level that is significantly lower than the foraging clicks produced by these animals. To date, most of the studies of beaked whale echolocation behavior, especially buzz production, have relied on analysis of data from acoustic recording tags placed on vocal animals. While tag data has allowed detailed description of the dive cycles and foraging behavior of the tagged animals, providing invaluable ground truth for other passive acoustic monitoring studies, it is of limited quantity. Tagging beaked whales is difficult and the spatial and temporal coverage of tagged animals remains sparse. Growing numbers of bottom-moored and bottom-mounted sensors are being used for passive acoustic monitoring and for the study of Md and Zc behavior and distribution. Buzzes from Md and Zc are detectable on such remote sensors and these buzz data can augment higher order studies, such as those on beaked whale habitat use and population health, as detected buzzes can serve for as a proxy for prey capture attempts.